Analysis of Factors that Influence Flat Construction Work - Arman Hari Susilomarto; Firdaus (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the factors that influence the success of building flats in Jambi Province. The sample for this research was staff and employees involved in the construction of flats, totaling 105 people. The method used is a quantitative method with the SEM-Smart-PLS analysis technique. The data used is primary and secondary data, hypothesis testing uses weight relations. The results of research regarding factors that influence construction work, namely financing, do not have a significant influence on the structure of building work. Labor does not have a significant influence on the structure of building work. Equipment has a positive and significant influence on the structure of building work. Materials have a positive and significant influence on the structure of building work. Financing, labor, equipment and materials have a positive and significant influence on the structure of building work